Response Activation and Inhibition in Patients With Prolactinomas: An Electrophysiological Study - Song, Jian; Cao, Chenglong; Wang, Yu; Yao, Shun; Catalino, Michael P.; Yan, Deqi; Xu, Guozheng; Ma, Lianting (Frontiers in Human Neuroscience, 2020)
Impairment of executive function has been reported in patients with prolactinomas. However, few studies have investigated the electrophysiological mechanisms of response activation and response inhibition in these patients. In this study, we employ an event-related potentials (ERPs) technique to quantitively assess the response activation and inhibition before and after surgical treatment of prolactinomas. A 64-electrode EEG skullcap was used to record brain activity in 20 pre-operative patients, 20 follow-up post-operative patients and 20 healthy controls (HCs) while performing the visual Go/Nogo task. As expected, we identified P300 across all study populations that could reflect the response activation and inhibition. Across the three groups, Nogo stimuli evoked larger frontal-central P300 than Go stimuli did. In contrast, Go trials elicited larger parietal P300 than Nogo trials did. The peak latency of P300 was significantly delayed in both pre- and post-operative groups compared to the HCs. The amplitude of P300 in both Go and Nogo conditions was significantly decreased in the pre-operative patients compared with that of the HCs. Six months post-operatively, prolactinoma patients showed an increase in the amplitude of P300 during both Go and Nogo tasks. These findings indicate that prolactinoma patients suffer from deficits in response activation and inhibition, which could be improved by surgical treatment.